'Weeaboo Japanese' : exploring English-Japanese language-mixing in online Japanese popular culture fandom : a thesis presented in partial fulfilment of the requirements for the degree of Master in Philosophy in Linguistics at Massey University, Albany, New Zealand - Gardiner, Rowan Elizabeth Arbuthnott (Massey University, 2019)
The complexities of a globalised modern society pose methodological and theoretical issues for linguistic research in areas such as Language Contact, Language-Mixing, and Sociolinguistics, due to the commodification and transmission of language and language features resulting in new language interactions. The boundary between definitions of language borrowing and code- switching is currently a matter of increased interest, particularly in terms of research identifying cases of language use involving unskilled participants. This study investigates and linguistically analyses the presence of Japanese language features within English language contexts that are produced by members of online discussion forums who are fans of Japanese popular culture, and for whom fluency in Japanese language is not assumed nor required for participation. Corpus linguistics techniques were employed on data gathered from two online sources in order to identify what linguistic features were present and establish their extent according to frequency. These same corpora were qualitatively analysed to establish community attitudes towards English-Japanese language mixing and what these results indicated in terms of policing and community norms, and overall what both the quantitative and qualitative results meant for how the language phenomena could be defined according to current theoretical paradigms. The results showed that the most frequent word class was nouns, and the semantic domains found were mostly related to Japanese fandom concepts that were topical to the forum, such as specific interests, clothing and fashion, food, media related terms, and religion and cultural terms. Most instances were single-word insertions, and where the few multi-word segments occurred they were specifically in reference to a negative stereotype within the community (weeaboo). This stereotype also indicated language policing was a factor affecting language use, and the results showed that while the Japanese language had high status, language use was socially restricted to specific situations and extents of use. The language phenomenon is described as mostly language borrowing behaviours, but as the words retain a high level of knowledge of related assignations and also occur concurrently with a few code-switching type behaviours, the usage-based approach where both elements are considered different aspects of the same continuum is seen as a preferable theoretical paradigm.
Keywords: English language; Foreign elements; Japanese language; Influence on foreign languages; Languages in contact; Popular culture; Japan; Electronic discussion groups; 470411 Sociolinguistics